Pengaruh Model Cooperative Integrated Reading and Composition dengan Media Puzzle Terhadap Minat Baca Peserta Didik Kelas III SDN Kestalan No.5 Surakarta Tahun Pelajaran 2022/2023” - Qinun Aufa; Sugiaryo Sugiaryo (Departement of Mathematics Education, 2023)
This pre-experimental research aims to find out how the effect of the Cooperative Integrated Reading and Composition Model with Media Puzzle has on the Reading Interest of Class III Students at SDN Kestalan No.5 Surakarta in the Academic Year 2022/2023. The research hypothesis is that the Cooperative Integrated Reading and Composition Model with Media Puzzle has an effect on the reading interest of third-grade students in the 2022/23 academic year at SDN Kestalan No.5 Surakarta. Pre-experimental research is a type of research in which the experimental class and the control class study Indonesian in different ways to see if students are interested in reading. For the 2022/23 academic year, 43 class III students at SDN Kestalan No.5 Surakarta took part in this research. After that it was decided that class III A would be the experimental group and class III B would be the control group. A closed questionnaire with a Likert scale (1-4) was used in this study. The questionnaire was tested first in class III A at SD Cengklik Surakarta in the 2022/2023 academic year before being used in research. The t test is used as a hypothesis test in this study. However, homogeneity and normality tests were previously carried out. The tcount value is 8.996 based on the t test results. With df=(n1+n2)-2 or (21+22)-2= 41 it can be compared with ttable, which is at a significant level of 5%, namely 1.683. The hypothesis proposed states that